2019
DOI: 10.1002/hpm.2731
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors influencing home delivery in the context of user‐fee abolition in Northern Ghana: Evidence from 2014 DHS

Abstract: Summary User‐fee exemption for skilled delivery services has been implemented in Ghana since 2003 as a way to address financial barriers to access. However, many women still deliver at home. Based on data from the 2014 Ghana Demographic and Health Survey, we estimated the prevalence of home delivery and determined the factors contributing to homebirths among a total of 622 women in the Northern region in the context of the user‐fee exemption policy in Ghana. Binary and multivariate logistic regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…For instance, a study in Guinea found a prevalence of 61.8% home deliveries among women [ 38 ]. Other studies in Ghana [ 34 ], Nigeria [ 39 ] and Ethiopia [ 32 ], identified a prevalence of 59, 62 and 67.2% of home deliveries among women respectively. The disparities in prevalence of home delivery in this study, compared to other previous studies could be due to differences in study population and samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a study in Guinea found a prevalence of 61.8% home deliveries among women [ 38 ]. Other studies in Ghana [ 34 ], Nigeria [ 39 ] and Ethiopia [ 32 ], identified a prevalence of 59, 62 and 67.2% of home deliveries among women respectively. The disparities in prevalence of home delivery in this study, compared to other previous studies could be due to differences in study population and samples.…”
Section: Discussionmentioning
confidence: 99%
“…Low socio-economic status, manifested in lack of formal education for both woman and partner, poorest wealth quintile and rural dwelling was linked with a higher likelihood of home delivery. Previous studies have also found factors such as lower wealth quintile [ 23 , 34 , 43 , 44 ], lack of education [ 45 48 ] and rural dwelling [ 44 , 49 , 50 ] as predictors of home delivery. In most of these studies, the possible reasons provided for the increased likelihood of home delivery among these cohorts of pregnant women is financial and geographical barriers to accessing health facility deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for this finding is that although giving birth at health facility is free in Ghana, costs such as supplies and medications, transportation, unofficial provider fees may deter women who live in low-income settings. These are costs not covered under the current user-fee exemption policy and hence pregnant women may rather opt for TBAs, whose services are often cheap and considered negotiable [27].…”
Section: Discussionmentioning
confidence: 99%
“…The available literature in Ghana has identified that women's choice of place for delivery is shaped by individual-level factors such as maternal age, education, religion, ANC utilization, and maternal knowledge [16][17][18]. However, the factors which influence women's choice of delivery place operate at various levels including household and community [19][20][21].…”
Section: Introductionmentioning
confidence: 99%